APPLICATION OF THE SPECTROMETRIC METHOD FOR CALCULATING THE DOSE RATE FOR CREATING CALIBRATION HIGHLY SENSITIVE INSTRUMENTS BASED ON SCINTILLATION DETECTION UNITS - R. V. Lukashevich; G. A. Fokov (Приборы и методы измерений, 2017)
Devices based on scintillation detector are highly sensitive to photon radiation and are widely used to measure the environment dose rate. Modernization of the measuring path to minimize the error in measuring the response of the detector to gamma radiation has already reached its technological ceiling and does not give the proper effect. More promising for this purpose are new methods of processing the obtained spectrometric information. The purpose of this work is the development of highly sensitive instruments based on scintillation detection units using a spectrometric method for calculating dose rate.In this paper we consider the spectrometric method of dosimetry of gamma radiation based on the transformation of the measured instrumental spectrum. Using predetermined or measured functions of the detector response to the action of gamma radiation of a given energy and flux density, a certain function of the energy G(E) is determined. Using this function as the core of the integral transformation from the field to dose characteristic, it is possible to obtain the dose value directly from the current instrumentation spectrum. Applying the function G(E) to the energy distribution of the fluence of photon radiation in the environment, the total dose rate can be determined without information on the distribution of radioisotopes in the environment.To determine G(E) by Monte-Carlo method instrumental response function of the scintillator detector to monoenergetic photon radiation sources as well as other characteristics are calculated. Then the whole full-scale energy range is divided into energy ranges for which the function G(E) is calculated using a linear interpolation.Spectrometric method for dose calculation using the function G(E), which allows the use of scintillation detection units for a wide range of dosimetry applications is considered in the article. As well as describes the method of calculating this function by using Monte-Carlo methods and the features of its application. The results of the calculation function G(E) for the detection unit on the basis of NaI(Tl) detector (Ø40 mm, h = 40 mm) to use it as a comparator for kerma rate in the air certification of low intenseе photon radiation fields.